STRATEGI PENGEMBANGAN MADRASAH ALIYAH PLUS SUNAN GIRI KOTA SALATIGA - Agusman, Agusman (Nusantara Hasana Journal, 2025)
This study discusses the development strategy of Madrasah Aliyah Plus Sunan Giri in Salatiga City as an effort to improve the quality of pesantren-based education. The background of this study stems from the need for Islamic educational institutions to adapt to the times without abandoning their Islamic identity. The objectives of this study are to analyze the development strategies implemented, assess the results and their impact on improving the quality of education, and identify the factors that support and hinder their implementation. The research objective focuses on the development strategies implemented and the extent to which they have been successful in improving the quality of the institution. The research method uses a qualitative descriptive approach with a case study at Madrasah Aliyah Plus Sunan Giri.The data was obtained through observation, in-depth interviews, and documentation, then analyzed through reduction, coding, and verification stages to ensure the validity of the findings. The results of the study show that the madrasah implements five main development strategies, namely the development of an integrative curriculum, improvement of educational resources and teaching staff, improvement of facilities and infrastructure, guidance for students, and transparent and accountable financial management. The implementation of these strategies has had a positive impact on improving the quality of learning, teacher and student motivation, and the image of the institution in the community. In conclusion, the success of the development of Madrasah Aliyah Plus Sunan Giri lies in professional, participatory, and sustainable management, although there are still obstacles in terms of funding and limited facilities that need to be continuously improved.